2014
DOI: 10.1039/c4tb00956h
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-graft-poly(l-lactic acid) nanoparticles for efficient delivery of anti-cancer drugs

Abstract: BA-loaded cellulose-graft-poly(l-lactic acid) nanoparticles were fabricated by employing cellulose and poly(l-lactic acid) as materials and betulinic acid as a model drug. The nanoparticles have appropriate size and excellent antitumor activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…Furthermore, the uptake of CE‐g–PMMA–BA NPs enhanced the area under curve (AUC) by 3.1‐fold compared with native BA. In another study, BA‐loaded cellulose‐graft poly( l ‐lactic acid) NPs (CE‐g–PLLA–BA NPs) were developed in order to improve efficacy . In vitro cytotoxicity studies in human lung carcinoma (A549) and LLC cell lines demonstrated superior cytotoxicity of CE‐g–PLLA–BA NPs compared with native BA.…”
Section: Nanoformulations For Betulinic Acid Deliverymentioning
confidence: 99%
“…Furthermore, the uptake of CE‐g–PMMA–BA NPs enhanced the area under curve (AUC) by 3.1‐fold compared with native BA. In another study, BA‐loaded cellulose‐graft poly( l ‐lactic acid) NPs (CE‐g–PLLA–BA NPs) were developed in order to improve efficacy . In vitro cytotoxicity studies in human lung carcinoma (A549) and LLC cell lines demonstrated superior cytotoxicity of CE‐g–PLLA–BA NPs compared with native BA.…”
Section: Nanoformulations For Betulinic Acid Deliverymentioning
confidence: 99%
“…21,22 It has been demonstrated that IgE antibody plays an important role in mediating type Ⅰ hypersensitivity reaction. Some natural anti-cancer drugs such as docetaxel, paclitaxel, and teniposide cyclosporine were usually associated with a high incidence of the type Ⅰ hypersensitivity reaction.…”
Section: Side Effortmentioning
confidence: 99%
“…23 The DLE of the drug-loaded nanoparticles were listed in Table. 1. In this study, the amphiphilic conjugate mPEG-DGN self-assembled into nanoparticles in aqueous phase for loading HCPT (Scheme.…”
Section: Characterization Of the Nanoparticlesmentioning
confidence: 99%
“…However, a large proportion of those electrochemical reactions require the noble-metal based catalysts, which are expensive and rare in the earth, that limited the industry application of those new energy system. [21][22][23][24][25] Therefore, there are still critical challenges in the fabrication of alternative electrocatalysts with high performance based on non-noble metal materials.…”
Section: Introductionmentioning
confidence: 99%